Refusal of Polygamy Permit in Religious Court Decision: Criticism of Gender Justice Against Judge’s Legal Reasoning - Santoso, Lukman; Amaliyah, Arij; Huda, Miftahul (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2023)
This study aims to determine and analyse the judges' considerations using gender justice in the Decision of the Madiun District Religious Court Number 1512/Pdt.G/2022/PA.Kab.Mn. Normatively, the permissibility of polygamy rests on the wife's consent and the husband's ability to be fair. In this case, the problem started with applying for a polygamy permit after the Applicant married his second wife. Argumentation: The Applicant, who was married before applying polygamy, was considered unlawful. This is doctrinal legal research with a case, conceptual, and statutory approach. Data sources for this research are court decisions, laws and regulations, books, journals, and research results. This research provides a conceptual basis for judges in making decisions on applications for polygamy licenses based on gender equity so that justice in society is created objectively.